Trends and predictors in methadone maintenance treatment dropout in Shanghai, China: 2005–2011. (July 2013) - Ren, Jinma; Ning, Zhen; Asche, Carl V.; Zhuang, Minghua; Kirkness, Carmen S.; Ye, Xiangyang; Fu, Jie; Pan, Qichao
Abstract Background: The methadone maintenance treatment (MMT) program has been implemented in Shanghai since 2005. This study aims to portray the trend of MMT dropout and identify predictive factors that may influence dropout in Shanghai MMT clinics, which could assist in the intervention strategy development. Methods: A retrospective evaluation was used in the Shanghai component of the National MMT data management system between January 1, 2005 and December 31, 2011. The Cox model for recurrence events was employed to estimate hazard ratio (HR) predicting dropout during the follow-up period. Results: Of all 6169 participants, 63% dropped out of the program at least once (ranging from 0 to 10 times), and 74% of them did not return by the end of this study. The average monthly incidence rate of dropout was 4.4% with a range from 0 to 9.3%. Adjusted analyses demonstrated that the individuals with methadone tapering didn't have a greater probability of dropping out compared to those with stable dosage (HR = 1.07, 95% CI: 0.90–1.27). However, there was a higher dropout rate among younger individuals (<30 years vs. ≥50 years old; HR = 1.41, 95% CI: 1.16–1.71), among those who were less educated (HR = 1.48, 95% CI: 1.17–1.87), among those who shared needles with others (HR = 1.29, 95% CI: 1.06–1.58), among those whose urine tested positive for opiates (HR = 1.69, 95% CI: 1.51–1.89), and among those who had a low average methadone dose at the initial stable stage of treatment (≤35 mg/day vs. >65 mg/day; HR = 1.39, 95% CI: 1.19–1.63). Conclusions: Shanghai has been facing the challenge of keeping a high MMT retention rate. Increasing the use of methadone tapering after a stable treatment stage with sufficient dosage could be attempted in the MMT program, as well as considering comprehensive interventions among specific populations, such as young, poorly educated, opiate-positive and needle sharing individuals.